Sharia principles in counternarratives of charity-based terrorism financing - Khoirunnisa, Tsabita Afifah; Nurish, Amanah; Priyanto, Sapto (Center for Islamic Economics and Development Studies [P3EI], 2026)
Purpose – This study aims to formulate a sharia-based counternarrative framework to address charity-based terrorism financing while reducing the suspicion and stigmatization of Islamic philanthropic institutions within the Countering the Financing of Terrorism (CFT) regime. It seeks to bridge the gap between terrorism financing scholarship and Islamic philanthropy by offering a normative model that strengthens institutional legitimacy and enables the public to distinguish between credible charitable organizations and high-risk fundraising entities.Methodology – This qualitative library study draws on academic literature on terrorist financing and Islamic philanthropy, as well as relevant policy and regulatory frameworks in Indonesia. Through conceptual synthesis and normative analysis, the study integrates key Sharia principles governing zakat, infaq, and shadaqah into a structured counternarrative framework.Findings – The study finds that dominant approaches to countering terrorist financing largely emphasize legal compliance and risk-based regulation, whereas existing counternarrative frameworks—particularly religious moderation—focus on interfaith harmony and ideological tolerance. These approaches inadequately address how humanitarian appeals are exploited in charity-based terrorist financing. To respond to this gap, the paper formulates a normative model grounded in six sharia principles: ukhuwwah, ‘adalah, ri’ayah, maslahah, tawazun, and shumuliyah.Implications – Embedding these principles within counternarratives can strengthen public trust, reduce the stigmatization of Islamic charities, and support clearer differentiation between legitimate philanthropic institutions and exploitative fundraising entities.Originality – This study bridges terrorism financing research and Islamic philanthropic ethics by shifting the discourse from securitized compliance toward legitimacy-based counter-narrative construction in the Indonesian context.